2010
DOI: 10.1007/s12011-010-8767-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Dietary Iodine Intake on Lipid Metabolism in Mice

Abstract: The present study has been designed to investigate the impact of dietary iodine intake on lipid metabolism in mice, including iodine deficiency and iodine excess. Different amounts of iodine mixed in the drinking water were continuously administered to mice. The body weights and the levels of urinary iodine were measured 8 months after the treatment. Thyroid hormones in the serum were detected by chemiluminescence immunoassay. Serum total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…However, this study highlighted that those with low UIC had increased risk of lipid abnormalities. In an animal study conducted by Zhao et al [ 21 ], they confirmed the decreasing effect of high iodine intake on hyperlipidemia in mice, but did not investigate that kind of effect in humans. Therefore, adding to our results, it will be necessary to make further efforts to identify a casual effect of high iodine exposure on lipid concentration among those with iodine excess.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this study highlighted that those with low UIC had increased risk of lipid abnormalities. In an animal study conducted by Zhao et al [ 21 ], they confirmed the decreasing effect of high iodine intake on hyperlipidemia in mice, but did not investigate that kind of effect in humans. Therefore, adding to our results, it will be necessary to make further efforts to identify a casual effect of high iodine exposure on lipid concentration among those with iodine excess.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the impact of actual dietary iodine intakes and individual’s iodine status on serum lipids is worth further investigation as well. Lastly, the study using mice reported that the effect of iodine intake on lipid metabolism may vary depending on the sex of the mice, mentioning needs of considering interaction between iodine status and the sex hormone in the lipid metabolism [ 21 ]. Further investigation is needed to explore the effect of these interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of total lipids, especially cholesterol and triglycerides in the blood (Table 4) might be due to the effect of iodine which enhances thyroid gland function and its activity. The iodine deficiency may lead to insufficient production of thyroid hormones and vice-versa, which affects on lipid metabolism Zhao et al, (2011), as there is a positive relationship between the activity of the thyroid gland and its hormones and iodine intake (El-Wardany et al, 2011). Słupczyńska et al, (2014) mentioned that thyroid hormones play an important role in regulating lipid metabolism.…”
Section: H/l Ratiomentioning
confidence: 99%
“…Moreover, some studies have reported that high dietary iodine is associated with adverse effects upon productive performance, egg quality, and blood cholesterol in laying hens (Lichovnikova et al 2003;Lewis 2004;Yalçin et al 2004;Flachowsky et al 2006;Opali nski et al 2012;R€ ottger et al 2012;Saki et al 2012). Rodent studies have suggested that the association of excessive dietary iodine and elevated plasma cholesterol and triglycerides levels is mediated by oxidative stress pathways (Venditti et al 1997;Joanta et al 2006;Zhao et al 2011). However, confirmation of this association in poultry studies is still pending.…”
Section: Introductionmentioning
confidence: 99%